Sustainable Cementless Brick - Zaki Albar, Muhammad Zafri Albar (IRC, 2019)
The study aims to produce sustainable cementless brick. Producing brick from waste materials is a great way to contribute to a more sustainable environment. To meet the aim of the study, the study approaches several potential brick binders which are plastics and geopolymers to completely replace cement as a brick binder. Multiple bricks with different mixes were produced and the samples were tested under water absorption test and compressive strength test